The complete book of essential oils and aromatherapy : over 800 natural, nontoxic, and fragrant recipes to create health, beauty, and safe home and work environments - Worwood, Valerie Ann, 1945- (Novato, California : New World Library, 2016)
"A necessary resource for anyone interested in alternative approaches to healing and lifestyle, this book contains more than 800 easy-to-follow recipes for essential oil treatments. Now, completely updated, the best book on the topic available anywhere has just gotten better. No one has provided more thorough and accurate guidance to the home practitioner or professional than Valerie Ann Worwood. In her clear and positive voice, Worwood offers readers tools to address a huge variety of health issues, including specific advice for children, women, men, and seniors, as well as self defense against microbes and contaminants, dealing with emotions, care for the home and workplace, and specialist advice for athletes, dancers, travelers, cooks, gardeners, and animal lovers. Worwood offers us her expertise in the use of essential oils in beauty and spa treatments, as well as providing profiles for 125 essential oils, 37 carrier oils, and more. Since the first publication of the book 25 years ago, the positive impact of essential oil use has become increasingly recognized as scientific researchers throughout the world explore essential oils and their constituents for their unique properties and uses"--
Chapter 1. Medicines out of the Earth -- Chapter 2. The basic care kit -- Chapter 3. The self-defense kit -- Chapter 4. Occupational oils for the working man and woman -- Chapter 5. Emotional rescue -- Chapter 6. The basic travel kit -- Chapter 7. The gentle touch for babies, children, and teenagers -- Chapter 8. A woman's natural choice -- Chapter 9. The natural choice for men -- Chapter 10. Essential help in the maturing years -- Chapter 11. Assertive oils for sports, dance, and exercise -- Chapter 12. Major health concerns -- Chapter 13. The fragrant way to beauty -- Chapter 14. The home spa -- body beautiful -- Chapter 15. Fragrant care for your home -- Chapter 16. Cooking with essential oils -- Chapter 17. Natural health for animals -- Chapter 18. Gardens for the future -- Chapter 19. Carrier oils and hyrdolats -- Chapter 20. The essential oils and absolutes -- Chapter 21. Safety information -- Appendix 1. The Chemistry of Essential Oils -- Appendix 2. Glossary of therapeutic properties.
Includes bibliographical references and index.
105293
Keywords: Aromatherapy; Health & Fitness -- Aromatherapy; Health & Fitness -- Reference; Reference -- Handbooks & Manuals; Body, Mind & Spirt -- Healing -- General